UMA ANÁLISE ECONÔMICA DA SOCIALIDADE NOS CONTRATOS PRIVADOS RELACIONAIS (Revista Direito em Debate, 2019)
This article aims to explain the importance to encourage the sociality in a kind of long term contracts, based on the Economic Analysis of Law - LAE. Although Richard Posner was credited as the author of the LAE, it earned more relevance in 1960, as of the publication of The problem of the social cost, that was written by Ronald Coase, that examined the reciprocal harmful effects that happens by the exploitation of productive activities. In this view, is necessary to look to mitigate endogenous transactional costs, to promote self-composition and legislative and/or judicial decisions able to foment surplus value and, consequently, sustainable development. To understand the current theme, we must study classical, neoclassical and long term contractual systems, some species of contracts, as well as the business entropies and the manegement of risks. For that, an exploratory approach is used, through deductive method, all per a qualitative bibliographical and videographical research.
Keywords: LAE; Sociality; Relational contract; Surplus value; Development